Parents’ Experiences of Caring for Children with Congenital Rubella Syndrome (CRS) in Remote and Rural Areas of Indonesia - Petrus Kanisius Siga Tage; Herliana Monika Azi Djogo; Erna Febriyanti; Yulia Martiningsih Karmila Letor; Maria Yoanita Bina; Maria Yasintha Goa Goa; Angela Muryanti Gatum (Nurse Media Journal of Nursing, 2023)
Background: Parents of children with Congenital Rubella Syndrome (CRS) in rural areas face limited access to medical care and specialised services, financial difficulties, social isolation, and stigma. Research on their experiences is limited.Purpose: This study explores parents’ experiences of caring for their children with CRS in rural areas of Indonesia.Methods: The research used a descriptive phenomenological approach, purposive sampling to collect parents of children with CRS from the shelter, and snowball sampling for other participants. Inclusion criteria included parents who cared for CRS children over than two years old, could express their experiences, and spoke Indonesian. Twenty-five parents participated in an in-depth semi-structured interview. The data were analysed using the Colaizzi method.Results: This research found that parents caring for sick children in rural areas experienced life-altering situations that affected their mental health. In addition, caring for sick children also caused emotional disturbances and tension in family life. Other challenges included getting proper treatment for their child, especially in remote rural areas, and difficulty to reach health services. Therefore, proper mental health treatment and support were essential for parents who cared for sick children in rural areas.Conclusion: This study describes complexities of parents’ experiences of caring for children with CRS, such as difficulty to accept the child's condition and feeling burdened by their child’s case. Further studies are needed to understand cultural influences and expand the study area.